World economy and world polotics, 1924 - 1931 : from reconstruction to collapse - Ziebura, Gilbert (New York, 1990)
This book has had a long gestation. The questions that it poses arose for the first time in connection with a research project which I headed between 1963 and 1974 at the Central Institute 6 of the Free University of Berlin. We set out to study the foreign policy of the four most important European countries, Germany, France, Italy and Great Britain, during the 1930s with special attention to the critical year of 1936. The aim was to elaborate further on the reasons for the eventual collapse of the international system. We abandoned the well-worn paths of traditional political and diplomatic history to the extent that we focused attention from the outset on the domestic factors and the global economic factors that conditioned the foreign policy of these countries. This meant, among other things, that we needed to determine the impact of the Great Depression on the ability of the major parties to the Versailles System to steer a particular foreign policy. This was a pivotal question that previously had not received the consideration it deserved.
Keywords: Economic history 1918 - 1945